In/Between: Phillipi Photographed - Hammond, Michael Brian (Michaelis School of Fine Art, 2024)
Philippi, a farming area outside Cape Town, is strained by social relations and spatial concerns, the pressures of development, industry, farming, sand mining and environmental issues. This photographic project investigates how the people of Philippi live in their immediate space, where particular historical, social and political influences mark their identities. These identities are constructed through the legacy of apartheid and manifest themselves in socio-economic and racial dynamics. This photographic project focuses on the Phillipi area and its people. I chose the horticultural area of Philippi in the Cape Flats for its complex and intricate socio-political structure. During this investigation I made a photobook In/ between, which speaks to topics of land and identity in the microcosm of Philipi, but also in the broader macrocosm of South Africa. In this document, I investigate the position of the photobook within the contemporary arts, with a particular focus on the South African photobook. I also look at the shifting understanding of documentary photography in South Africa, and my position within its' traditions. Making the photobook In/between allowed me the opportunity to explore photography as a tool for self-reflection and pursuing my own understanding of the world around me; to move away from a more traditional journalistic approach to other ways of telling a story through the medium of photography. This document situates, contextualises and explicates my visual research for this project.